2017
DOI: 10.1051/0004-6361/201629040
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and chemical study of planetary nebulae and H II regions in NGC 3109

Abstract: Aims. We present high-resolution spectroscopy of a number of planetary nebulae (PNe) and H ii regions distributed along the dwarf irregular galaxy NGC 3109 and compare their kinematical behavior with that of H i data. We aim to determine if there is a kinematical connection among these objects. We also aim to determine the chemical composition of some PNe and H ii regions in this galaxy and discuss it in comparison with stellar evolution models.Methods. Data for eight PNe and one H ii region were obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Gradients based on oxygen abundances have been also calculated from PN data although for the case of highly ionized objects a correction due to the presence of O +3 is required. However, it has been shown that O in PNe may be enriched (or depleted) due to stellar nucleosynthesis, particularly in low-metallicity environments (Peña, Stasińska, & Richer 2007;Flores-Durán, Peña, & Ruiz 2017) and also in Galactic PNe with carbon-rich dust (Delgado-Inglada et al 2015). Therefore metallicity gradients derived from O abundances in PNe could be perturbed by stellar nucleosynthesis and thus this element could be not adequate to analyze the chemical gradients and the evolution of galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradients based on oxygen abundances have been also calculated from PN data although for the case of highly ionized objects a correction due to the presence of O +3 is required. However, it has been shown that O in PNe may be enriched (or depleted) due to stellar nucleosynthesis, particularly in low-metallicity environments (Peña, Stasińska, & Richer 2007;Flores-Durán, Peña, & Ruiz 2017) and also in Galactic PNe with carbon-rich dust (Delgado-Inglada et al 2015). Therefore metallicity gradients derived from O abundances in PNe could be perturbed by stellar nucleosynthesis and thus this element could be not adequate to analyze the chemical gradients and the evolution of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore metallicity gradients derived from O abundances in PNe could be perturbed by stellar nucleosynthesis and thus this element could be not adequate to analyze the chemical gradients and the evolution of galaxies. Apparently Ne abundances are also modified by stellar nucleosynthesis in lowmetallicity environments (Karakas 2010;Milingo et al 2010;Flores-Durán, Peña, & Ruiz 2017). On the other hand, Ar and S abundances in PNe are not expected to be modified in such processes during the PN progenitor lifetime, although their abundance determinations have large uncertainties due to large uncertainties in the ionization correction factors when only one ion (Ar ++ or S + ) is observed (Delgado-Inglada, Morisset, & Stasińska 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lines of [O ii] λλ3726+29 are summed in the tables even if observations allow one to separate the lines. The only PNe where this doublet is resolved are: one object in NGC 3109 observed by Peña et al (2007b) and the sample studied by Flores-Durán et al (2017), the PNe in the LMC and SMC reported by Tsamis et al (2003), and the SMC sample observed by Shaw et al (2010).…”
Section: Line Fluxesmentioning
confidence: 90%
“…Chemical abundance determinations in these systems are mainly limited to H II regions (e.g., Izotov & Thuan 1999;Kniazev et al 2005;Magrini et al 2005;van Zee & Haynes 2006;Guseva et al 2011;Haurberg et al 2013;Berg et al 2012) and to a few supergiant stars (Venn et al 2001(Venn et al , 2003Kaufer et al 2004;Leaman et al 2009Leaman et al , 2013, which probe a look-back time of at most ∼10 Myr. Chemical abundance studies of planetary nebulae (e.g., Magrini et al 2005;Peña et al 2007;García-Rojas et al 2016;Flores-Durán et al 2017;Annibali et al 2017) and unresolved star clusters (e.g., Strader et al 2003;Puzia & Sharina 2008;Sharina et al 2010;Hwang et al 2014) provide a valuable tool to explore more ancient epochs and have been attempted in a few dwarf irregulars. The H II region and young supergiant tracers indicate typically low [α/Fe] ratios, as expected in galaxies that have formed stars at a low rate over a long period of time and where galactic winds may have possibly contributed to the expulsion of the α-elements.…”
Section: [α/Fe] Ratiosmentioning
confidence: 99%